Differences in Semantic Memory Encoding Strategies in Young, Healthy Old and MCI Patients - Suzin, Gil; Ravona-Springer, Ramit; Ash, Elissa L.; Davelaar, Eddy J.; Usher, Marius (Frontiers in Aging Neuroscience, 2019)
Associative processes, such as the encoding of associations between words in a list, can enhance episodic memory performance and are thought to deteriorate with age. Here, we examine the nature of age-related deficits in the encoding of associations, by using a free recall paradigm with visual arrays of objects. Fifty-five participants (26 young students; 20 cognitive healthy older adults; 9 patients with Mild Cognitive Impairment (MCI)) were shown multiple slides (experimental trials), each containing an array of 9 common objects for recall. Most of the arrays contained 3 objects from three semantic categories, each. In the remaining arrays the nine objects were unrelated. Eye fixations were also monitored during the viewing of the arrays, in a subset of the participants. While for young participants the immediate recall was higher for the semantically related arrays, this effect was diminished in healthy elderly and totally absent in MCI patients. Furthermore, only in the young group did the sequence of eye fixations show a semantic scanning pattern during encoding, even when the related objects were non- adjacent in the array. Healthy elderly and MCI patients were not influenced by the semantic relatedness of items, as observed by a lack of semantic scanning. The results support the encoding of association aging-deficit hypothesis.